1975
DOI: 10.1002/anie.197505501
|View full text |Cite
|
Sign up to set email alerts
|

ESR Proof of the Antiaromaticity of a Cyclopropenyl Radical

Abstract: C 0 M M U N I C AT1 0 N S pectation that even a cyclopropenyl radical with 3x-electrons has antiaromatic characterf5! By known methods[61 we have prepared di-tert-butyl-(3,5-ditert-butylpheny1)cyclopropenylium perchlorate ( 1 1 and from this by means of LiAIH4 1,3-di-tert-butyl-2-(3,5-di-tert-butyl-pheny1)cycloprepene (2). Photolysis of a solution of (2) in di-tert-butyl peroxide['] at -30°C affords a radical (3) whose Dedicated to Professor K. Dimroth on the occasion of his 65th birthday The simplest represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…185,186 The 2,3-di-tert-butyl-1-(3,5-di-tert-butylphenyl)cyclopropenyl radical has a π-structure, presumably because of the extensive benzylic delocalization. 187 Thus, even these very crude models have significant localization of the π-electron density and this can only be accentuated by perturbations resulting from the inclusion of heteroatoms in the bonding framework. The indication is therefore clear: the transition states for the five-center-five-electron and three-center-three-electron migrations will have substantial localization of electron density, i.e., polarization as in 436 and 437.…”
Section: Computational Studies and Esr Considerationsmentioning
confidence: 99%
“…185,186 The 2,3-di-tert-butyl-1-(3,5-di-tert-butylphenyl)cyclopropenyl radical has a π-structure, presumably because of the extensive benzylic delocalization. 187 Thus, even these very crude models have significant localization of the π-electron density and this can only be accentuated by perturbations resulting from the inclusion of heteroatoms in the bonding framework. The indication is therefore clear: the transition states for the five-center-five-electron and three-center-three-electron migrations will have substantial localization of electron density, i.e., polarization as in 436 and 437.…”
Section: Computational Studies and Esr Considerationsmentioning
confidence: 99%
“…C 3 H 3 is an indispensable radical in reactions involving cyclic aromatic hydrocarbons, soot formation processes, and some combustion reactions. For example, it is an important intermediate in forming the aromatic ring through recombination of two propargyl radicals. , In addition, C 3 H 3 has been observed as one of the products in the C­( 3 P) + C 3 H 6 reaction in the atmospheres of Titan and giant planets as well as in the interstellar medium . Numerous experimental and theoretical studies , have reported on this radical because of its significance. Previous studies ,,, show that several isomers of C 3 H 3 exist, including propargyl radical, cyclopropenyl radical (c-C 3 H 3 ), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on the electron spin resonance (ESR) spectrum , and ionization potentials (IPs) of C 3 H 3 have been reported. On the other hand, the electronic structure of C 3 H 3 has also been investigated ,, , , using various methods such as Hartree–Fock theory (HF), density functional theory (DFT), , coupled-cluster theory (CC), , configuration interaction (CI), multiconfiguration self-consistent field (MCSCF), and complete active space SCF (CASSCF). , Most of these studies focus on the aromaticity or antiaromaticity of C 3 H 3 , since aromaticity is closely related to its stability.…”
Section: Introductionmentioning
confidence: 99%
“…Structural distortion or Jahn–Teller distortion along the e′ mode provides ethylene and allylic structures possessing C 2 v symmetry, where the ground states belong to A 2 and B 1 irreducible representations, respectively. These structures are connected by an in-plane distortion via a C s path on the pseudorotation surface. Detailed results can be found in appropriate reports. …”
Section: Introductionmentioning
confidence: 99%